Remembering Stalin's Victims : Popular Memory and the End of the USSR - Smith, Kathleen E. (Book collections on Project MUSE., 2009)
In Remembering Stalin's Victims, Kathleen E. Smith examines how government reformers' repudiation of Stalin's repressions both in the 1950s and in the 1980s created new political crises. Drawing on interviews, she tells the stories of citizens and officials in conflict over the past. She also addresses the underlying question how societies emerging from repressive regimes reconcile themselves to their memories. Soviet leaders twice attempted to liberalize Communist rule and both times their initiatives hinged on criticism of Stalin. During the years of the Khrushchev "thaw" and again during Gorbachev's glasnost, antistalinism proved a unique catalyst for democratic mobilization. The battle over the Soviet past, Smith suggests, not only illuminates the dynamic between elite and mass political actors during liberalization but also reveals the scars that totalitarian rule has left on Russian society and the long-term obstacles to reform it has created